SPATIAL PATTERNS OF ENSO IMPACT ON INDONESIAN RAINFALL - Edvin Aldrian (Jurnal Sains & Teknologi Modifikasi Cuaca, 2002)
A monthly temporal and spatial assesment on ENSO impact on Indonesian rainfall hasbeen done. The study uses monthly ensemble averages of El Nino and La Nina years from 1961 to 1993. There are 6 El Niño years and 5 La Niña years during that period. Indonesia experiences negative ENSO influences from April on both El Niño (warm phase) and La Niña (cold phase). The influences of ENSO reach their peaks in August and September by both types of events and decay afterward. The influences diminish totally by December. Since the influences occur in the dry season, El Niño contributes a negative impact, while La Niña a positive impact to the Indonesian climate. The maximum spatial extension of ENSO reaches almost all parts of Indonesia except north Sumatera and some parts of Kalimantan. There is an indication of a negative influence of ENSO to the onset of Asian monsoon in the Southeast Asian.Kajian bulanan secara temporal dan geografis tentang pengaruh ENSO terhadap curahhujan Indonesia telah dilakukan. Penelitian ini memakai nilai rata-rata gabungan bulanan dari tahun El Niño dan La Niña dari 1961 hingga 1993. Ada 6 tahun El Niño dan 5 tahun La Niña pada perioda tersebut. Indonesia menerima pengaruh negatif dari ENSO mulai April pada tahun ENSO. Pengaruh ENSO mencapai puncaknya pada bulan Agustus dan September pada keduanya dan menurun setelahnya. Pengaruhnya benar-benar hilang pada bulan Desember. Karena pengaruh ENSO terjadi pada musim kering, El Niño memberikan kontribusi negative terhadap iklim Indonesia, sementara La Niña memberikan kontribusi positive. Luasan daerah pengaruh ENSO yang maksimal terjadi di hampir seluruh wilayah Indonesia kecuali bagian utara Sumatera dan sebagian Kalimantan. Ada indikasi pengaruh negative dari ENSO terhadap kedatangan muson Asia ke wilayah Asia Tenggara.